Fear, depression, and well-being during COVID-19 in German and South African students: A cross-cultural comparison - Holm-Hadulla, Rainer M.; Mayer, Claude-Hélène; Wendler, Hannes; Kremer, Thomas L.; Kotera, Yasuhiro; Herpertz, Sabine C. (Frontiers in Psychology, 2022)
Various studies have shown a decrease in well-being and an increase in mental health problems during the COVID-19 pandemic; however, only a few studies have explored fear, depression, and well-being cross-culturally during this time. Accordingly, we present the results of a cross-cultural study that (1) compares these mental health scores for German and South African students, (2) compares the correlations among them, and (3) identifies COVID-19 fear, well-being, and depression predictors. German and South African societies differ from each other socio-culturally, politically, and economically. Their university systems also differ to a large extent. University students in both countries completed the Fear of COVID-19 Scale, the World Health Organization-Five Well-Being Index (WHO-5), and the Patient Health Questionnaire-9 (PHQ-9). Welch’s t-test, correlation, and multiple regression analyses were performed. (1) German students were found to have statistically lower levels of COVID-19 fear and depression, but lower levels of general well-being than South African students. (2) In both samples, fear of COVID-19 was negatively correlated with well-being and positively associated with female gender and depression. (3) Additionally, female gender, depression, and lower well-being were identified as predictors of COVID-19 fear in both samples. The findings indicate that the fear of COVID-19 is associated with and varies according to gender, depression, and well-being across cultures, and that the difference in the intensity of fear between German and South African students may be partly explained by cultural and contextual differences. These findings can create a deeper understanding of the pandemic’s impact on student communities and may be used by mental health practitioners and researchers to develop and apply culture-specific interventions.